JUDICIAL RESTRAINT DAN CONSTITUTIONAL INTERPRETATION TERHDAP KOMPETENSI MENGADILI PELANGGARAN PEMILIHAN UMUM TERSTRUKTUR, SISTEMATIS, DAN MASIF - Winata, Muhammad Reza (Jurnal Legislasi Indonesia, 2020)
The political contestation of 2019 General Election of President and Vice-President had political conflicts and election violations that violates the values and principles of democracy. Constitutional Court decision No. 01 / PHPU-PRES / XVII / 2019 has ended the political and legal process of the Presidential Election, but the Structured, Systematic, and Massive (TSM) election violations which are the main legal issues still a public discourse. The research questions to be answered is First, how is the application of judicial restraints on the development of competencies adjudicating TSM election violations? Second, what are the constitutional interpretations and the legal consequences of the decision? The research method used is juridical normative with a doctrinal, regulation, and cases approach. The results of the study found that the Court previously had the tendency for judicial activism to actively adjudicating TSM election violations, but at this time there was a tendency for judicial restraint from adjudicating TSM election violations. However, the Constitutional Court actually conducts conditionally judicial restraints because it requires the Constitutional Court is able to adjudicating TSM election violations if the authorized institution does not exercise its authority properly. Furthermore, in Presidential Election Decision, the Constitutional Court actually conducted a constitutionality review without through authority judicial review the law against the 1945 Constitution, based on textual and structural interpretation methods. This decision final characteristic, so that it has legal consequences to generally binding (erga omnes) and becomes a jurisprudence for the next general election case.